2009
DOI: 10.21897/rmvz.350
|View full text |Cite
|
Sign up to set email alerts
|

Resistencia a antibióticos de bacterias aisladas de biopelículas en una planta de alimentos

Abstract: RESUMENObjetivo. Evaluar la resistencia a antibióticos y la capacidad de formación de biopelículas de bacterias aisladas en una planta de producción de alimentos. Materiales y métodos. Se tomaron muestras de 3 zonas diferentes, en una planta procesadora de alimentos; en la lavadora de canastas, la mesa de producción y en la banda empacadora. Se aislaron e identificaron las bacterias presentes en cada una de las tres zonas y se determinó la capacidad formadora de biopelículas por medio de cuantificación celular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
2
0
4
Order By: Relevance
“…Such a distribution had already been observed in a smaller group of strains [29]. Other studies with different Bacillus species have also shown variable capacities to form biofilms in vitro [6,25,32]. It is important to point out that more than 90% of the studied Bt strains were able to form biofilms.…”
Section: Adhesion Capacity Of Bacillus Thuringiensis Spores and Its Rsupporting
confidence: 55%
“…Such a distribution had already been observed in a smaller group of strains [29]. Other studies with different Bacillus species have also shown variable capacities to form biofilms in vitro [6,25,32]. It is important to point out that more than 90% of the studied Bt strains were able to form biofilms.…”
Section: Adhesion Capacity Of Bacillus Thuringiensis Spores and Its Rsupporting
confidence: 55%
“…65% of isolates had an index ≥ 0.2, indicating that the bacterium has multiple resistance (Vanegas et al, 2009). These outcomes have a huge impact when selecting empiric treatment of these infections.…”
Section: Resultsmentioning
confidence: 99%
“…(31) About a third of the methicillin-resistant isolates were also resistant to other antibiotics including macrolides, lincosamides, quinolones, aminoglycosides, rifamycins, oxazolidinones, nitrofurans and antifolates. In addition, if a MAR index value >0.2 can be considered a multiple antimicrobial resistance characteristic (58), the presence of these multidrug-resistant strains could support the emergence of the three hypothetical scenarios described above.…”
Section: Discussionmentioning
confidence: 99%